Vascular Streak Dieback of Cocoa and its Management - Ajay Kumar K M (Department of Plant Pathology, College of Horticulture, 1996)
Vascular streak dieback (VSD) is a destructive disease of cocoa. Corticium culture medium, Water agar, Potato dextrose agar gave promising results in isolation of the pathogen. Petiole and midrib gave maximum success in isolation. Potato dextrose agar and Corticium culture media supported the growth of the fungus. Fusarium sp. And Colletotrichum gloeosporioides were the major contaminants interfering in the isolation of VSD. The morphological characters of the pathogen were studied from the sporophores occurring on naturally infected cocoa plants. Based on these characters, the pathogen causing VSD was identified as Oncobasidium theobromae Talbot and Keane. The disease produced various typical symptoms on leaves and stems of infected plants like pale green colour of leaves and subsequent yellowing with green islets, defoliation, brown marks on the scars of fallen leaves, axillary bud growth of the infected stem, rusty discolouration of cambium, vascular streak, whitish sporophores on the leaf scar of fallen infected leaves and finally the death of the infected twig. Histopathological studies showed the presence of fungal mycelium in the xylem vessels. Transmission studies by grafting and budding revealed no establishment of buds or grafts. But there was vascular streaking. No seed transmission was observed. In general Kitazin and Bavistin as a seed treatment had an effect on the height of plant and leaf production. Evaluation of cocoa types planted at three seed gradens indicated that some of them possess resistance/tolerance against VSD. Variation in disease incidence and intensity of VSD was noted in germplasm VI. Calixin spraying had an effect in preventing the incidence of the disease in seedlings.